2014
DOI: 10.1039/c3cp54247e
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic investigation and molecular docking study on the interaction of hen egg white lysozyme with liposomes of saturated and unsaturated phosphocholines probed by an anticancer drug ellipticine

Abstract: Interaction of hen egg white lysozyme with different liposomes made of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and 2-oleoyl-1-palmitoyl-sn-glycero-3-phosphocholine (POPC) was studied by circular dichroism (CD), steady state and time resolved fluorescence spectroscopy. We used anticancer drug ellipticine and studied its entrapment and release from liposomes upon interaction with lysozyme. The molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…Conformational changes in lysozyme in the presence of TBO were carried out using CD spectral studies in far and near‐UV CD regions. The CD spectrum of native lysozyme shows characteristic bands at 208 nm and 222 nm in the far‐UV region (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational changes in lysozyme in the presence of TBO were carried out using CD spectral studies in far and near‐UV CD regions. The CD spectrum of native lysozyme shows characteristic bands at 208 nm and 222 nm in the far‐UV region (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that TBO when used as a mouth rinse may get released into the environment which in turn might produce adverse effects in fish and other aquatic life . Recently, the binding of drugs with lysozyme has been studied extensively by many groups and which explore the actual interaction and binding site of drugs in protein cavity . Therefore, the precise binding characteristics of antitumor drug (TBO) with lysozyme are critical to understanding its pharmaco‐ and toxicokinetics at the site of its action.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Other activities include anti-inflammatory, antiviral, antiseptic, antihistamine, and antineoplastic effects. [25][26][27][28] Such studies are important for the development of small molecules that can act as effective inhibitors of the aggregation of amyloidogenic proteins. [22][23][24][25] The details of the structure of Lyz, domains and amino acids in the protein have been described in detail in a recent study.…”
Section: Introductionmentioning
confidence: 99%
“…The docking simulations were performed considering rigid macromolecule (SOD1 dimer/monomer) and a flexible ligand (curcumin) [48]. The binding site of curcumin was recognized using blind docking [49][50][51] by setting the grid size to 126 × 126 × 126 along the X, Y and Z axis respectively with 0.564 Å grid spacing. Lamarckian Genetic Algorithm (LGA) as implemented in Autodock software [52] was utilized for prediction of the binding mode.…”
Section: Docking Of Sod1 and Curcumin Using Autodockmentioning
confidence: 99%